Calculation of Resonant Radiation Power of a Direct Sodium Lamp With Low Pressure - V.K, Sveshnikov; A.F, Bazarkin; A.V, Kurenschikov (International Journal of Engineering and Technology, 2018)
They consider the calculation technique for the resonance radiation power of a direct low-pressure sodium lamp with a sickle-shaped discharge tube cross-section. The calculation of the sodium discharge radiation power is difficult in such a tube, as compared with the calculation in a cylindrical shape tube. The dependence of the relative output of sodium discharge resonant radiation occurring in equivalent discharge tubes in the form of a parallelepiped and a cylinder is based on the involvement of the theory by M. Cayless. The obtained results were used to determine the power of DNaO-85M lamp resonant radiation. They presented the scheme of the device to study the influence of the tube geometry on sodium discharge power. It is shown that the power of the resonance radiation generated by an equivalent discharge will be the greater, the larger the cross section of the discharge tube. The discrepancy between the calculated and the experimental data for resonant radiation power determination in a crescent-shaped tube is less than 4%.Â Â